Care, breeding and management of laboratory zebrafish (Danio rerio) (Journal of Laboratory Animal Science, 2019)
During the past few decades, zebrafish has gained respectable popularity as a vertebrate animal model in  modern biology research. Several biological features inherited in zebrafish have invited attention of scientific  community to use them in genetics and developmental biology research to substitute laboratory mouse. The  origin of the laboratory zebrafish is traced to Ganges in East India and Burma, a fresh water fish found in  slow stream and rice paddy. The zebrafish can easily adopt laboratory conditions and breed very well even in  fluctuating environmental conditions. In research laboratory, zebrafish can be reared in less expensive glass  aquarium or using more advance recirculating water system. The recirculating water system has many inbuilt  features which help to provide optimum physical environment necessary for rearing fish in the healthy condi tions. In the present paper, attempts have been made to compile brief information about zebrafish breeding,  embryo & larval culture, feeding, water quality control, physical environment and fish health monitoring  necessary for rearing zebrafish in the research laboratory.
Keywords: zebrafish; management; breeding